Can Gender Differences Be Evaluated in a Rhesus Macaque (Macaca mulatta) Model of Focal Cerebral Ischemia? - Murphy, Stephanie J (American Association for Laboratory Animal Science, 2008)
Gender differences, sex steroid effects, and sex-specific candidate therapeutics in ischemic stroke have been studied in rodents but not in nonhuman primates. In this feasibility study (n = 3 per group), we developed a model of transient focal cerebral ischemia in adult male and female rhesus macaques that consistently includes white matter injury. The animals also were used to determine whether gender-linked differences in histopathologic outcomes could be evaluated in this model in future, larger preclinical trials. Histologic brain pathology was evaluated at 4 d after 90 min of reversible occlusion of the middle cerebral artery (MCA). MCA occlusion was accomplished by using a transorbital approach and temporary placement of an aneurysm clip. Male and female rhesus macaques 7 to 11 y of age were studied. Baseline and intraischemic blood glucose, systolic blood pressure, heart rate, oxygen saturation, end-tidal CO(2), and rectal temperatures were not different among groups. The variability in injury volume was comparable to that observed in human focal cerebrovascular ischemia and in other nonhuman primate models using proximal MCA occlusion. In this small sample, the volume of injury was not different between male and female subjects, but observed variability was higher in female caudate nucleus, putamen, and hemisphere. This report is the first to compare cerebral ischemic outcomes in female and male rhesus macaques. The female rhesus macaque ischemic stroke model could be used after rodent studies to provide preclinical data for clinical trials in women.